2016
DOI: 10.1589/jpts.28.3416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of motor imagery on excitability of spinal neural function and its impact on the accuracy of movement-considering the point at which subjects subjectively determine the 50%MVC point

Abstract: [Purpose] This study aimed to examine the effect of motor imagery on the accuracy of motion and the excitability of spinal neural function. [Subjects and Methods] Thirty healthy volunteers (males, 15; females, 15; mean age, 20.3 ± 1.0 years) were recruited. F-waves was recorded at rest, while holding a sensor, and while using motor imagery. Next, subjects learned 50% maximum voluntary contraction. The pinch force was measured without visual feedback before and after motor imagery. F-waves were analyzed with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…However, this report did not provide an explanation of how spinal motor neuron excitability controls movement because it only focused on spinal motor neuron excitability. In our previous study, the excitability of spinal motor neurons was increased during MI, while precision pinch force control skills did not improve 27 . Additionally, increased excitability of spinal motor neurons during MI was not always associated with improved precision pinch force control skills.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, this report did not provide an explanation of how spinal motor neuron excitability controls movement because it only focused on spinal motor neuron excitability. In our previous study, the excitability of spinal motor neurons was increased during MI, while precision pinch force control skills did not improve 27 . Additionally, increased excitability of spinal motor neurons during MI was not always associated with improved precision pinch force control skills.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, 21 healthy participants (13 men and 8 women; mean age: 24.8 ± 5.5 years) were included to ensure that the actual sample size was greater than the calculated sample size. We did not exclude any participants due to an error of more than 5% (error [%] = [exerting pinch force – 50% MVC] / 50% MVC × 100) from the 50% MVC to examine the time required for accurate adjustment 27 . The participants were determined to be right-handed using the Edinburgh Handedness Inventory to control the condition of hand dominance (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, persistence and the F/M amplitude ratio are regarded as indices of the swimmer. Moreover, Dickstein et al [14] reported gait speed to be improved using motor imagery in hemiparesis patients with Cardio Vascular Disease. Thus, motor imagery may improve muscle strength, motor function, muscle ductility, gait speed, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Mental rotation makes the brain move objects in order to help understand what they are and where they belong. The aim is to rotate the image without requiring the use of higher cognitive function and attention and to think of simple visual images to further promote the activation of the brain [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%